THE INFLUENCE OF THE TIME OF LIGHT TRAP APPLICATION ON THE EFFECTIVENESS OF CAPTURINGMetisa Plana BAGWORM AT PABATU PLANTATION PT. PERKEBUNAN NUSANTARA IV - Hasibuan, Henry Budi; Rey Naldi , Lesmana; Sulthon, Parinduri; Maisarah (Institut Teknologi Sawit Indonesia, 2024)
Light traps are a way to detect early pest attacks in the field. A light trap is a device used to catch or attractinsects. Functions to determine the presence or number of insect populations on plantation land. The use oflight traps as an environmentally friendly alternative for pest control, insect attraction to color is one way ofadapting insects in nature. Insect adaptations aim to protect themselves from predators. This research wasconducted at PT. X Kebun Afdeling 4, North Sumatra. This research aims to determine the time and lightintensity in the light trap application that is most effective in controlling bagworm imago. The method used isthe descriptive method, consisting of 3 different times, namely 19.00-21.00 WIB, 23.00-01.00 WIB, and 04.00-06.00 WIB. The parameter observed was the number of trapped bagworm (Metisa plana) imago. From theresearch results, the time for applying light traps at 04.00-06.00 WIB is the time for applying light traps thatis effective in controlling imago of bagworms (Metisa plana) with a total catch of 242 individuals during 10days of research at PT. X Afdeling Gardens 4